Safeguarding wealth (Hifdh al mal) and its role in sustainable economic development in the OIC countries - Haneef, Mohamed Aslam; Mohd Amin, Ruzita; Abdullah Yusof, Selamah; Khan, Foyasal (2015)
Sustainable economic development is mainly about balanced development of economy, society an environment which is achievable through ending poverty and improving well-being through access to education, employment, information, better health and housing, and reducing inequality while moving towards sustainable consumption and production. Except few countries, the performances of the OIC Countries in terms of these essential factors of sustainable economic development is generally not sound and healthy. One of the key barriers, inter alia, to sustainable economic development in the OIC countries is a conventional economic development mindset especially to follow the prescriptions of neo-liberal free market economy of self-interest and rationalism. To achieve sustainable economic development, therefore, needs to focus on the shari’ah based Islamic economic system because the very objective (maqasid) of the Sharī‘ah is to promote the well-being of the people through serving the interests of all human beings and saving them from harm. Imām al-Ghazālī classified the maqasid into five major categories. These are: safeguarding their faith (dīn), their self (nafs), their intellect (‘aql), their posterity (nasl), and their wealth (māl). These maqāsid or goals are all mutually interrelated and they can together help promote real human well-being. The objective of this paper, however, is to discuss one of the maqasid, Safeguarding Wealth, in greater details and its role in sustainable economic development in the OIC countries. As methodology of the paper, various databases and conventional as well as Islamic economic literature will be studied to find out the necessary requirements of sustainable economic development in the OIC countries.